Micropollutant adsorption from water with engineered porous ceramic architectures produced by additive manufacturing and coated with natural zeolite. (10th June 2020) - König, Roger; Spaggiari, Marco; Santoliquido, Oscar; Principi, Pamela; Bianchi, Giovanni; Ortona, Alberto
Abstract: Treatment of waste and drinking waters has gained importance in both emerging and industrialized countries. New pharmaceutical products, industrial processes, agricultural activities are reducing water quality. To solve these problems we propose an efficient and thus economical purification method which uses commercial available natural zeolites as coating material on engineered porous ceramic substrates produced by additive manufacturing. The filters were produced varying the coating thickness and processing parameters such as calcination time and temperature. A testing device was assembled to investigate the filters' performance by exposing them in flowing water (240 Lh -1 ). The micropollutant adsorption was tested in three different water matrices (distilled water, surface water and wastewater treatment plant effluent). A range of 0.05 mg NH4 –N g −1 up to 3.1 mg NH4 – NH4 –N g −1 zeolite of ammonium nitrogen was observed on the processed filters. Good filter stability expressed as weight loss (<5%) was observed. The adsorption of ten tested micropollutants showed an overall efficiency of 41.5% and 43% on the surface modified zeolite filters. Natural zeolite filters showed good specific adsorption capacity for metoprolol, citalopram, venlaflaxine and clarithromycin whereas the surface modified zeolite (SMZ) filters adsorb better hydrochlorothiazide, diclofenac, candesartan, mecoprop and irbesartan. Highlights: Ceramic filter prototypes were produced by AM and coated with zeolite. Optimum coating was achieved with a thermal treatment at 500 °C for 4 h. The adsorption capacity was characterized with OMP elimination performance. Low OMP adsorption competition with natural organic matter is shown. Over 80% elimination of the filters (untreated and surfactant treated) was reached.